2013
DOI: 10.1371/journal.pone.0076468
|View full text |Cite
|
Sign up to set email alerts
|

Cytoprotective Effect of Recombinant Human Erythropoietin Produced in Transgenic Tobacco Plants

Abstract: Asialo-erythropoietin, a desialylated form of human erythropoietin (EPO) lacking hematopoietic activity, is receiving increased attention because of its broader protective effects in preclinical models of tissue injury. However, attempts to translate its protective effects into clinical practice is hampered by unavailability of suitable expression system and its costly and limit production from expensive mammalian cell-made EPO (rhuEPOM) by enzymatic desialylation. In the current study, we took advantage of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
43
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(49 citation statements)
references
References 70 publications
(97 reference statements)
6
43
0
Order By: Relevance
“…It has been reported that EPO glycoforms produced from tobacco showed a 2-fold increase in cytoprotective effect compared with that produced from CHO cells. Glycan analysis of the EPO expressed in tobacco cells revealed a significant amount of high-mannose EPO (32). In this perspective, the homogeneous …”
Section: Discussionmentioning
confidence: 87%
“…It has been reported that EPO glycoforms produced from tobacco showed a 2-fold increase in cytoprotective effect compared with that produced from CHO cells. Glycan analysis of the EPO expressed in tobacco cells revealed a significant amount of high-mannose EPO (32). In this perspective, the homogeneous …”
Section: Discussionmentioning
confidence: 87%
“…Leaf tissues harvested from greenhouse grown transgenic tobacco line A56-5 with high expression of asialo-rhuEPO P (Kittur et al 2013) were used for DNA, RNA and protein purification throughout the studies unless otherwise stated.…”
Section: Methodsmentioning
confidence: 99%
“…The asialo-rhuEPO P peak fractions were collected and further purified using an IAC column. Asialo-rhuEPO P in each IAC fraction was determined using a sandwich ELISA as described previously (Kittur et al 2013). Residual BSA in the purified fraction was removed using Melon ™ gel BSA removal kit (Thermo Scientific, Waltham, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations